2004
DOI: 10.1007/s10266-004-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sounds generated by a dental turbine and a stream on regional cerebral blood flow and cardiovascular responses

Abstract: Effects of sound generated by a dental turbine and a small stream (murmur) and the effects of no sound (null, control) on heart rate, systolic and diastolic blood pressure, and hemodynamic changes (oxygenated, deoxygenated, and total hemoglobin concentrations) in the frontal cortex were measured in 18 young volunteers. Questionnaires completed by the volunteers were also evaluated. Near-infrared spectroscopy and the Finapres technique were employed to measure hemodynamic and vascular responses, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
(13 reference statements)
2
20
0
Order By: Relevance
“…However, in our previous studies, as mentioned before (Miyazaki et al, 1999;Mishima et al, 2004), changes in physiological parameters by the inhalation of wood odor or the sound of murmuring water were observed within 60 to 90 seconds. Though these were the results of laboratory experiments, it can be expected that the impacts of "Shinrin-yoku" on physiological response would be obtained in a shorter time.…”
Section: ) Forestry and Forest Products Research Institute 2) Graduamentioning
confidence: 87%
See 1 more Smart Citation
“…However, in our previous studies, as mentioned before (Miyazaki et al, 1999;Mishima et al, 2004), changes in physiological parameters by the inhalation of wood odor or the sound of murmuring water were observed within 60 to 90 seconds. Though these were the results of laboratory experiments, it can be expected that the impacts of "Shinrin-yoku" on physiological response would be obtained in a shorter time.…”
Section: ) Forestry and Forest Products Research Institute 2) Graduamentioning
confidence: 87%
“…The authors have tried to examine the pleasant feelings that natural objects induce in humans by conducting physiological investigations. From studies dealing with the five senses separately, we have clarified that the smell of Japanese cedar wood lowered blood pressure and regional cerebral blood flow in the prefrontal area (Miyazaki et al, 1999), and the sound of murmuring water lowered blood pressure (Mishima et al, 2004). As Frumkin (2001) showed that a deep-seated connection between the natural world and humans was unsurprising from an evolutionary perspective, we assume that human physiological functions have had to adapt to the natural environment; thus, it is somehow a stressor to live in modern "artificial" society.…”
Section: Introductionmentioning
confidence: 99%
“…Mishima et al [37] compared the changes in brain activity and systolic blood pressure caused while listening to the sound of a turbine (dental implement), representing an artificial sound, or to a stream, representing a natural sound. No sound was introduced in the control session, i.e., the subjects heard no sound.…”
Section: Auditory Stimulationmentioning
confidence: 99%
“…4 Among the traumatic factors that may explain fears of dentistry are odors 5 and sounds. 6 In addition, Kleinknecht et al 7 showed that the sources of fear during dental treatment include the anesthetic needle and drill. Psychological trauma resulting from experiences may negatively infl uence patient perception during future treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Mishima et al, 6 the effects of sound generated by a dental turbine and the effects of no sound (null, control) on heart rate, systolic and diastolic blood pressure, and hemodynamic changes (oxygenated, deoxygenated, and total hemoglobin concentrations) in the frontal cortex were measured in young volunteers. NIRS and the Finapres technique were used to measure hemodynamic and cardiovascular responses, respectively.…”
Section: Introductionmentioning
confidence: 99%